Indian captive, Indian king : Peter Williamson in America and Britain - Shannon, Timothy J. (Timothy John), 1964- (Harvard University Press, 2018)
In 1758, Peter Williamson appeared in the streets of Aberdeen, Scotland, dressed as a Native American Indian and telling a remarkable tale. He claimed that as a young boy many years earlier, he had been kidnapped from the city and sold into slavery in America. In performances he gave in taverns and coffeehouses and in a printed narrative he peddled to his audiences, Williamson described his serial tribulations on the fringes of the British Empire as an indentured servant, Indian captive, soldier, and prisoner of war. In his performances and publications, Williamson offered British audiences a distinctly plebian perspective on the British Empire in North America. His unique career capitalized on the curiosity that the Seven Years' War ignited among the British public for news and information about America and its Native inhabitants, but his reputation for fabrication also made his contemporaries and historians reluctant to believe him. Indian Captive, Indian King is the first biography of Williamson to separate the fact from fiction in his tale and explain what it tells us about how the working people of eighteenth-century Britain, so often depicted as victims of empire, found their own ways to create lives and exploit opportunities within it.--